Hard Rock Tunnel Boring - Bruland, Amund (Fakultet for ingeniørvitenskap og teknologi, 2000)
The main purpose of the thesis work has been to improve the existing prediction models and to provide a toolbox for the TBM tunnelling industry (project owners, consultants, contractors, manufacturers, etc.) to be used through all phases of a project: • Preliminary and feasibility studies • Project design and optimisation • Site investigations • Tendering and contract • Construction • Possible disputes or claims. The various reports of the thesis treat various subjects of TBM tunnelling. Combined with other estimation models published in the Project Report Series from the Department of Building and Construction Engineering, the reports of the thesis provides a reliable and practical tool to be used for: • Estimating net penetration rate and cutter life • Estimating construction time and costs, including risk or uncertainty • Assessing risk with regard to deviation or variation in estimated rock mass boreability, machine parameters and tunnelling performance • Designing auxiliary systems such as ventilation, muck transport, etc. • Establishing and managing price regulation in contracts • Verifying machine performance • Back-mapping and verification of the geological conditions • Collecting, normalising and analysing of rock samples, machine performance data and cutter wear data. The thesis work has not been focused on basic principles, theoretical modelling or laboratory experiments of rock cutting with disc cutters, although observations and results from field studies are presented and analysed in [11]. Several other researchers and institutions have covered those topics. To be mentioned here is the prominent and comprehensive research done at Colorado School of Mines in the USA and at Luleå University of Technology in Sweden. Both institutions have a series of publications ranging over three decades in this area. dr.ing. dr.ing.